Increasing energy efficiency by geometric modification of hoe-type furrow opener - R Rahimzadeh (Ferdowsi University of Mashhad, 2016)
Introduction Direct planting becomes more common in the recent years, because it conserves soil and water as well as it saves energy and time. However, this technology needs special implements such as seed planter. Given that direct planting is practiced in undisturbed lands, so it was needed to design a special furrow opener. In order to obtain a suitable furrow opener this experiment was conducted in rain-fed Agricultural Research Institute in Maragheh. Materials and Methods Most of seed planters that are used for cultivation in rain fed conditions are equipped by hoe-type furrow opener. Hoe-type furrow openers have good penetration in hard and dry soils. However, they do not have the ability for direct planting. Hoe-type furrow opener was chosen as a model. Then by changing the geometric form of the depth to width ratio (d/w), the two openers were designed. In the first design, which was called O1 two wings and a narrow blade acting as a coulter were added in front of the hoe-type furrow opener. In the second design, which was called O2, in addition to the O1 modification, furrow opener width was decreased and a disk blade was added for seed sowing (Fig. 1).